Macrophage-Derived Adenosine Deaminase 2 Correlates with M2 Macrophage Phenotype in Triple Negative Breast Cancer - Kutryb-Zajac, Barbara (Int J Mol Sci, 2021)
Several lines of evidence suggest that altered adenosine deaminase (ADA) activity, especially its ADA2 iso-enzyme, is associated with malignant breast cancer (BC) development. Triple-negative breast cancer (TNBC) is currently the most challenging BC subtype due to its metastatic potential and recurrence. Herein, we analyzed the sources of ADA iso-enzymes in TNBC by investigating the effects of cell-to-cell interactions between TNBC cells, macrophages, lymphocytes, and endothelial cells. We also examined the potential relationship between ADA activity and cancer progression in TNBC patients. In vitro analyses demonstrated that the interactions of immune and endothelial cells with MDA-MB-231 triple negative BC cells modulated their extracellular adenosine metabolism pattern. However, they caused an increase in the ADA1 activity, and did not alter ADA2 activity in cancer cells. In turn, the co-culture of MDA-MB-231 cells with THP-1 monocyte/macrophages, Jurkat cells, and human lung microvascular endothelial cells (HULEC) caused the increase in ADA2 activity on THP-1 cells and ADA1 activity on Jurkat cells and HULEC. Clinical sample analysis revealed that TNBC patients had higher plasma ADA2 activities and lower ADA1/ADA2 ratio at advanced stages of cancer development than in the initial stages, while patients with hormone receptor positive, HER2 negative (HR+HER2-), and triple positive (HR+HER2+) breast cancers at the same stages showed opposite trends. TNBC patients also demonstrated positive associations between plasma ADA2 activity and pro-tumor M2 macrophage markers, as well as between ADA1 activity and endothelial dysfunction or inflammatory parameters. The analysis of TNBC patients, at 6 and 12 months following cancer treatment, did not showed significant changes in plasma ADA activities and macrophage polarization markers, which may be the cause of their therapeutic failure. We conclude that alterations in both ADA iso-enzymes can play a role in breast cancer development and progression by the modulation of extracellular adenosine-dependent pathways. Additionally, the changes in ADA2 activity that may contribute to the differentiation of macrophages into unfavorable pro-tumor M2 phenotype deserve special attention in TNBC.